Early Changes in Platelet Size and Number in Patients with Acute Coronary Syndrome - Sušilović Grabovac, Zora; Baković, Darija; Lozo, Mislav; Pintarić, Irena; Dujić, Željko (International Journal of Angiology, 2017)
A strong relationship exists between acute coronary syndrome (ACS) and platelets (PLTs) volume. Mean platelet volume (MPV) is a parameter of PLT functions and a marker for increased PLT activation. The aim of this study was to determine early changes in number of total PLT and MPV in different manifestation of ACS and to find out predictive value of MPV in the spectrum of ACS. This was a prospective study. One hundred thirty-four ACS patients were enrolled, 76 of them finished the study. PLT and MPV in patients with unstable angina, non-ST elevation, and ST elevation myocardial infarctions were determined on arrival and 1, 3, 72 hours, and 7 days after the admission to hospital. There was decrease in PLT and MPV in all three groups after 3 hours of arrival in hospital in comparison with admission values. In the later time period (72 hours and 7 days), there was an increase in PLT and MPV only in patients with acute myocardial infarction (AMI). We have revealed completely new dynamics in early changes in MPV and PLT count in patients with AMI. Biphasic changes were found in early phase after admission to the hospital. Fast response in these parameters raises new questions about their origin.
Keywords: mean platelet volume; platelet count; large platelets; platelet activation; platelet function; acute coronary syndrome; early changes